Episodic hydrocarbon charge in tight Mississippian reservoirs of Central Oklahoma, USA: Insights from oil inclusion geochemistry. (January 2021) - Atwah, Ibrahim; Mohammadi, Sahar; Moldowan, J. Michael; Dahl, Jeremy
Abstract: The unforeseen discovery of substantial hydrocarbons in ultra-tight Mississippian reservoirs in Oklahoma testifies to the complexity of the hydrocarbon charge across the flanks of the Nemaha Uplift. Based on crude oil and fluid-inclusion chemistry, the hydrocarbons at the western side of the Nemaha Uplift consist of highly-mature, thermally-cracked and less-mature uncracked hydrocarbons (0.50–1.4% calculated vitrinite reflectance, Rc ). The oils are less mature on the eastern flank of the structure (0.5–0.7% Rc ). Based on distributions of biomarkers and higher diamondoid (composed of three adamantane cages or more) distributions, the hydrocarbons entrapped within reservoir fluid-inclusions are sourced from the Woodford Shale and also from Mississippian carbonates. To our knowledge, this is the first work to describe oil correlations using diamondoids inside fluid inclusions. Petroleum compositions in the ultra-tight Mississippian reservoirs are highly variable, which highlights the need for a thorough assessment of mechanisms controlling charge. By integrating oil and fluid inclusion geochemistry and fluid-inclusion microthermometry with basin modeling, we show that the primary controls are: (1) proximity to the source-rock kitchen(s), (2) episodic charging from Permian through Cretaceous time, and (3) mixing. Highlights: Hydrocarbon charge to the Mississippian reservoirs is examined through oil-inclusion geochemistry and microthermometry. Thermal maturity discrepancy is observed between fluid inclusions and produced crude oils from Mississippian carbonates. The timing of Mississippian reservoir-filling is inferred through combining fluid-inclusions with basin modeling techniques. First documentation of diamondoids occurrence in oil-bearing fluid inclusions.